The economic impact of potential migration policies in the UK after Brexit - Latorre, Maria C. (2019)
The bulk of studies which attempt to quantify the effects of Brexit focus on trade issues; however, very few of them have analysed migration. In this paper, we analyse the impact of several migration policies on GDP, GDP per capita, wages, national income and sectoral production in the UK, using what is technically called a general equilibrium analysis. We also analyse the impact at the macroeconomic level on the EU. We find that migration has the potential of deeply affecting economic activity in the UK. The more restrictive immigration policies are, the greater the losses in terms of GDP and Welfare. However, according to the text of the ‘joint agreement’ reached by the UK and EU on December 8 (2017), very restrictive policies seem to be ruled out. Nevertheless, after the ‘Windrush scandal’ some doubts about the final implementation of future UK migration policies remain. We also analyse mild migration policies which would only reduce the number of migrants received. Reductions in the number of EU immigrants between 42,000 and 87,000 per year would lead to foregone GDP increases in the UK between 0.08% and 0.17%. This impact should be considered cumulative across years in which the net inflows are reduced, so that negative effects for GDP and welfare can be substantial if the reduction in workers takes place during many years in a row. The UK currently has easy access to a large pool of workers coming from other EU member states, and UK managers have expressed that it is hard to replace EU talent in the short term. This suggests that if the political imperative for tighter immigration control cannot be avoided, gradual immigration restrictiveness will be less harmful for the UK’s economy and should be accompanied by additional efforts in education and workers’ training.